How home HIV testing and counselling with follow‐up support achieves high testing coverage and linkage to treatment and prevention: a qualitative analysis from Uganda. Issue 1 (28th June 2016) - Ware, Norma C; Wyatt, Monique A; Asiimwe, Stephen; Turyamureeba, Bosco; Tumwesigye, Elioda; van Rooyen, Heidi; Barnabas, Ruanne V; Celum, Connie L
Abstract : Introduction: The successes of HIV treatment scale‐up and the availability of new prevention tools have raised hopes that the epidemic can finally be controlled and ended. Reduction in HIV incidence and control of the epidemic requires high testing rates at population levels, followed by linkage to treatment or prevention. As effective linkage strategies are identified, it becomes important to understand how these strategies work. We use qualitative data from The Linkages Study, a recent community intervention trial of community‐based testing with linkage interventions in sub‐Saharan Africa, to show how lay counsellor home HIV testing and counselling (home HTC) with follow‐up support leads to linkage to clinic‐based HIV treatment and medical male circumcision services. Methods: We conducted 99 semi‐structured individual interviews with study participants and three focus groups with 16 lay counsellors in Kabwohe, Sheema District, Uganda. The participant sample included both HIV+ men and women ( N =47) and HIV‐uncircumcised men ( N =52). Interview and focus group audio‐recordings were translated and transcribed. Each transcript was summarized. The summaries were analyzed inductively to identify emergent themes. Thematic concepts were grouped to develop general constructs and framing propositional statements. Results: Trial participants expressed interest in linking to clinic‐based services at testing, but faced obstacles that eroded their initial enthusiasm. Follow‐up support by lay counsellors intervened to restore interest and inspire action. Together, home HTC and follow‐up support improved morale, created a desire to reciprocate, and provided reassurance that services were trustworthy. In different ways, these functions built links to the health service system. They worked to strengthen individuals' general sense of capability, while making the idea of accessing services more manageable and familiar, thus reducing linkage barriers. Conclusions: Home HTC with follow‐up support leads to linkage by building "social bridges, " interpersonal connections established and developed through repeated face‐to‐face contact between counsellors and prospective users of HIV treatment and male circumcision services. Social bridges link communities to the service system, inspiring individuals to overcome obstacles and access care.